2023
DOI: 10.3390/ijms24032961
|View full text |Cite
|
Sign up to set email alerts
|

A New Signature of Sarcoma Based on the Tumor Microenvironment Benefits Prognostic Prediction

Abstract: Sarcomas are a group of malignant tumors derived from mesenchymal tissues that display complex and variable pathological types. The impact of the immune properties of the tumor microenvironment (TME) on the prognosis, treatment, and management of sarcomas has attracted attention, requiring the exploration of sensitive and accurate signatures. In this study, The Cancer Genome Atlas (TCGA) database was searched to screen for an RNA sequencing dataset, retrieving 263 sarcoma and 2 normal samples with survival dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Furthermore, future studies should evaluate genetic markers as potential prognostic markers in patients with sarcoma following LSS. Previous studies have demonstrated the expression of programmed death-ligand 1 (PDL1), tumor protein 53 (TP53), and MYC protooncogene (MYC) in sarcomas and as potential targets for immunotherapy [17][18][19]. Given the altered expression of these markers in sarcomas, future studies should evaluate the prognostic ability of these markers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, future studies should evaluate genetic markers as potential prognostic markers in patients with sarcoma following LSS. Previous studies have demonstrated the expression of programmed death-ligand 1 (PDL1), tumor protein 53 (TP53), and MYC protooncogene (MYC) in sarcomas and as potential targets for immunotherapy [17][18][19]. Given the altered expression of these markers in sarcomas, future studies should evaluate the prognostic ability of these markers.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, specific immune cells, such as T cells, B cells, and natural killer (NK) cells, can exert antitumor effects, while others, like myeloid-derived suppressor cells (MDSCs), M2 macrophages, and regulatory T cells (Tregs), can promote tumor growth and metastasis. Thus, understanding the intricate interactions between OS and immune cells is crucial for developing effective immunotherapies [10,13].…”
Section: Introductionmentioning
confidence: 99%